A Novel Embryo Phenotype Associated With Interspecific Hybrid Weakness in Rice Is Controlled by the MADS-Domain Transcription Factor OsMADS8 - Kim, Sun Ha; Ji, Shi-Dong; Lee, Hyun-Sook; Jeon, Yun-A; Shim, Kyu-Chan; Adeva, Cheryl; Luong, Ngoc Ha; Yuan, Pingrong; Kim, Hyun-Jung; Tai, Thomas H.; Ahn, Sang-Nag (Frontiers in Plant Science, 2022)
A novel hybrid weakness gene, DTE9, associated with a dark tip embryo (DTE) trait, was observed in CR6078, an introgression line derived from a cross between the Oryza sativa spp. japonica ‘Hwayeong’ (HY) and the wild relative Oryza rufipogon. CR6078 seeds exhibit protruding embryos and flowers have altered inner floral organs. DTE9 was also associated with several hybrid weakness symptoms including decreased grain weight. Map-based cloning and transgenic approaches revealed that DTE9 is an allele of OsMADS8, a MADS-domain transcription factor. Genetic analysis indicated that two recessive complementary genes were responsible for the expression of the DTE trait. No sequence differences were observed between the two parental lines in the OsMADS8 coding region; however, numerous single nucleotide polymorphisms were detected in the promoter and intronic regions. We generated overexpression (OX) and RNA interference (RNAi) transgenic lines of OsMADS8 in HY and CR6078, respectively. The OsMADS8-OX lines showed the dark tip embryo phenotype, whereas OsMADS8-RNAi recovered the normal embryo phenotype. Changes in gene expression, including of ABCDE floral homeotic genes, were observed in the OsMADS8-OX and OsMADS8-RNAi lines. Overexpression of OsMADS8 led to decreased expression of OsEMF2b and ABA signaling-related genes including OsVP1/ABI3. HY seeds showed higher ABA content than CR6078 seeds, consistent with OsMADS8/DTE9 regulating the expression of genes related ABA catabolism in CR6078. Our results suggest that OsMADS8 is critical for floral organ determination and seed germination and that these effects are the result of regulation of the expression of OsEMF2b and its role in ABA signaling and catabolism.